2003
DOI: 10.1074/jbc.m211416200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate Lyase Is Involved in the Differentiation of F9 Embryonal Carcinoma Cells to Primitive Endoderm

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive lipid molecule that acts both extracellularly and intracellularly. The SPL gene encodes a mammalian S1P lyase that degrades S1P. Here, we have disrupted the SPL gene in mouse F9 embryonal carcinoma cells by gene targeting. This is the first report of gene disruption of mammalian S1P lyase. The SPL-null cells exhibited no S1P lyase activity, and intracellular S1P was increased approximately 2-fold, compared with wild-type cells. Treatment of F9 embryonal carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…Immunoblotting was performed as described previously (34,35) using anti-FLAG M2 (1.85 μg/mL) (Sigma), anti-calnexin 4F10 (1 μg/mL) (Medical & Biological Laboratories), or anti-GAPDH 6C5 (1 μg/mL; Ambion, Life Technologies) antibody as a primary antibody and an HRP-conjugated anti-mouse IgG F(ab') 2 fragment (1:7,500 dilution; GE Healthcare Life Sciences) as a secondary antibody. Labeling was detected using Pierce ECL Western Blotting Substrate (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was performed as described previously (34,35) using anti-FLAG M2 (1.85 μg/mL) (Sigma), anti-calnexin 4F10 (1 μg/mL) (Medical & Biological Laboratories), or anti-GAPDH 6C5 (1 μg/mL; Ambion, Life Technologies) antibody as a primary antibody and an HRP-conjugated anti-mouse IgG F(ab') 2 fragment (1:7,500 dilution; GE Healthcare Life Sciences) as a secondary antibody. Labeling was detected using Pierce ECL Western Blotting Substrate (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting-Immunoblotting was performed as described previously (30). Anti-SPHK1 (1/1000 dilution) (31), anti-FLAG M2 (1 g/ml; Stratagene), anti-Myc PL14 (1 g/ml; Medical & Biological Laboratories, Nagoya, Japan), anti-glyceraldehyde-3-phosphate dehydrogenase (1 g/ml; Ambion, Austin, TX), and anti-calnexin (H-10) antibodies (0.2 g/ml; Santa Cruz Biotechnology, Santa Cruz, CA) were used as primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that sphingosine kinase and S1P lyase, both of which are involved in S1P metabolism, were up-regulated during F9 PrE differentiation [19]. Moreover, S1P accumulation, resulting from the disruption of the S1P lyase gene or the overproduction of sphingosine kinase, resulted in accelerated of the PrE differentiation [19], suggesting that intracellular S1P is also involved in this process. Thus, it appears that extracellular and intracellular S1P cooperatively regulate PrE differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The pCE-puro plasmid, a mammalian expression vector, contains a puromycin-resistant gene used for selecting stable transformants [19]. The pCE-puro 3xFLAG-4 plasmid is a derivative of the pCE-puro plasmid and was designed to produce a C-terminal triple FLAG (3xFLAG)-tagged protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation